2009
DOI: 10.1002/cjoc.200990259
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐aldol Condensation of Cycloalkanones and Aromatic Aldehydes in the Presence of Nanoporous Silica‐based Sulfonic Acid (SiO2‐Pr‐SO3H) under Solvent Free Conditions

Abstract: The aromatic aldehydes underwent cross aldol condensation with cycloalkanones in the presence of a catalytic amount of nanoporous silica-based sulfonic acid (SiO 2 -Pr-SO 3 H) under solvent-free conditions to afford the corresponding α,α'-bis(substituted benzylidene)cycloalkanones in excellent yields with short reaction time without any side reactions. This method is very general, simple and environmentally friendly in contrast with other existing methods. SiO 2 -Pr-SO 3 H was proved to be an efficient heterog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…Afterward, V and Ph 3 COH produce intermediate VI, Ph 3 CCl and H 2 O. VI accordingly reacts with another activated aldehyde by Ph 3 CCl to afford the corresponding a,a 0 -bis(arylidene)cycloalkanone. The suggested mechanism is confirmed by the literature [29], and also by the fact that Ph 3 CCl was completely recovered unchanged and Ph 3 COH could not be identified after completion of the reaction as it could be observed on TLC by comparison with pure authentic samples. In another study, to demonstrate that Ph 3 CCl cannot convert to Ph 3 COH and HCl by the water produced during the reaction, and consequently HCl is not the real catalyst of the process, the solvent-free condensation of cyclohexanone with 3-nitrobenzaldehyde was examined in the presence of the expected amount of HCl produced by the reversible reaction of Ph 3 COH with H 2 O, at 110 8C, in which the product was obtained in 48% within 8 h. The reaction was also tested using Ph 3 COH wherein the reaction yield was 19% after 8 h. These evidences showed that HCl is not produced from Ph 3 CCl in these conditions, and that Ph 3 CCl is the real catalyst of this transformation.…”
supporting
confidence: 72%
“…Afterward, V and Ph 3 COH produce intermediate VI, Ph 3 CCl and H 2 O. VI accordingly reacts with another activated aldehyde by Ph 3 CCl to afford the corresponding a,a 0 -bis(arylidene)cycloalkanone. The suggested mechanism is confirmed by the literature [29], and also by the fact that Ph 3 CCl was completely recovered unchanged and Ph 3 COH could not be identified after completion of the reaction as it could be observed on TLC by comparison with pure authentic samples. In another study, to demonstrate that Ph 3 CCl cannot convert to Ph 3 COH and HCl by the water produced during the reaction, and consequently HCl is not the real catalyst of the process, the solvent-free condensation of cyclohexanone with 3-nitrobenzaldehyde was examined in the presence of the expected amount of HCl produced by the reversible reaction of Ph 3 COH with H 2 O, at 110 8C, in which the product was obtained in 48% within 8 h. The reaction was also tested using Ph 3 COH wherein the reaction yield was 19% after 8 h. These evidences showed that HCl is not produced from Ph 3 CCl in these conditions, and that Ph 3 CCl is the real catalyst of this transformation.…”
supporting
confidence: 72%
“…Silica sulfonic acid, nanoporous silica-based sulfonic acid and polymer supported sulfonic acid type catalysts are also employed for such condensations. Reaction times are reported to be in 3 -12 hour range [24][25][26]. In the present work, we have used covalently anchored sulfonic acid on silica gel (Catalyst 1, Scheme 1), which its applications have been reported in a few number of organic transformations [6,8,27,28] under solvent-free conditions to prepare α, ά-bis(substitutedbenzylidene) cycloalkanones (Scheme 2) in excellent yields, short reaction times and clean work up procedures.…”
Section: Introductionmentioning
confidence: 97%
“…24H 2 O , InCl 3 (Hazarika et al 2007), MnCl 2 (Heravi et al 2008), CuSO 4 .5H 2 O , Zn[(L)proline] , CAN (More et al 2006), Ga(OTf) 3 (Cai et al 2008), PEG-400 (Zhang et al 2010), Pd(OAc) 2 , MnO 2 (Raw et al 2003), keggin heteropoly acid (Huang et al 2009), and IBX (Heravi et al 2006) have been explored. In continuation of our studies (Mohammadi et al 2008(Mohammadi et al , 2009), on the application of nanoporous heterogeneous solid catalyst to organic synthesis, in this paper we want to report an efficient method for the preparation of quinoxaline derivatives using SBA-Pr-SO 3 H as a nanoporous heterogeneous acid catalyst. There are only a few reports about the application of several types of sulfonic acid functionalized ordered mesoporous silicas as nano acid catalyst in chemical transformations (Van Rhijn et al 1998, Das et al 2006.…”
Section: Introductionmentioning
confidence: 99%